Non-linear *-Jordan derivations on von Neumann algebras. Issue 3 (3rd March 2016) - Taghavi, Ali; Rohi, Hamid; Darvish, Vahid
Abstract : Let be a factor von Neumann algebra and be the *-Jordan derivation on, that is, for every, where, then is additive *-derivation.